EDFA-WDM optical network design system - Mohd Muzafar, Ismail; Mohd Azlishah, Othman; Zahriladha, Zakaria; Mohamad Harris, Misran; Maizatul Alice, Meor Said; Hamzah Asyrani, Sulaiman; Mohammad Noorazlan Shah, Zainudin; Mohamad Ariffin, Mutalib (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.